Past Presidential Elections and Colombo Stock Exchange - Rathnasingha, D.L.P.M.; Sivanathan, M. (My University, 2019)
. Introduction The stock market is an important part of any country’s economy that plays a pivotal role in the industrial growth by providing an optimum channelisation of funds 3/12 between the users and suppliers of funds. The performance of any stock market is influenced by economic, non-economic and political events in the country (Ismail and Suhardjo, 2001). Political events have been well known to be one of the main factors that affect the stock market. If the political system of a country is more stable, a business operating in that country will face less risk. Stable political situation has a low systematic investment risk, encourages growth, capital investment and improves overall economy’s performance (Betchel, 2009). The development and stable performance of the stock market attracts investments from both domestic and foreign investors (Levine and Zervos, 1998). Undoubtedly, their influence is followed by the price changes in the stocks which are traded in the stock exchange (Volodin and Kuranov and Yakubov 2017). Further, Bailey et al. (2005) and Frey and Waldenstrom (2004) also stated that political events have a strong effect on the returns and trading volume of the financial markets. Literatures on Stock market volatility to political events, were mainly based on the elections or civil war that took place in the country. For example, study by Karunarathna and Wijayanayake (2015) focused on the anomalies in the CSE due to presidential and general elections whilst, Kumara, Upananda and Rajib (2014) focused on the impact of ethnic war on the dynamic properties of stock return in the CSE. Therefore, the present study would provide coverage to Presidential Election events than what is available in the existing literature. Ismail and Suhardjo (2001) argue that mean adjusted returns model is superior to market model or market adjusted returns model in analyzing the movements of sector indices. Mean adjusted returns are actual returns minus a constant; the constant being the average return for that industry during its estimation period. The expected return is calculated using equation 1: where T is the number of days in the pre-determined estimation window, and t is the market index return on day t of the estimation window. Abnormal returns for each day of the event is calculated using equation 2: where ARt is the abnormal return in the market index in day t in the event window, Rt the return of the market index on day t of the event window, and R* is the mean return of the market over the number of days within the estimation period. The standard 4/12 deviation of the returns is calculated using equation 4: The significance of the abnormal returns during the event period is calculated using equation ASPI which is the value weighted price index of the entire share listed in the CSE is used to measure the movement of stock prices as an indicator to identify the stock market’s reaction in whole. Further, individual sector indices of BFI, BFT, CE, HT, DIV, MFG, MTR and PLT, etc., are used to measure the movement of stock prices under each sector in the CSE. Sectors are chosen based on their contribution to the market capitalisation of the CSE and depending on the availability of data.
Keywords: Presidential Elections; Colombo Stock Exchange; CSE; Sri Lanka